1990
DOI: 10.1523/jneurosci.10-11-03664.1990
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of ion channels involved in frequency selectivity and synaptic transmission at presynaptic active zones of hair cells

Abstract: Calcium ions serve as intracellular messengers in 2 activities of hair cells: in conjunction with Ca2(+)-activated K+ channels, they produce the electrical resonance that tunes each cell to a specific frequency of stimulation, and they trigger the release of a chemical synaptic transmitter. Our experiments indicate that both of these functions are conducted within a region that extends a few hundred nanometers around each presynaptic active zone. In focal electrical recordings from the plasma membranes of isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
525
0
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 595 publications
(565 citation statements)
references
References 96 publications
35
525
0
4
Order By: Relevance
“…Therefore, there is increasing interest in using intrinsic Ca 2ϩ -dependent proteins or processes to define the amplitudes and time course of [Ca 2ϩ ] i elevations. In the squid giant axon (Adler et al, 1991) and frog hair cells (Roberts et al, 1990), this approach has supported the theoretical expectation that [Ca 2ϩ ] i elevations during Ca 2ϩ influx are large and rapid. Furthermore, these studies have suggested that particular Ca 2ϩ -dependent processes are coupled closely to sites of Ca 2ϩ influx.…”
supporting
confidence: 53%
“…Therefore, there is increasing interest in using intrinsic Ca 2ϩ -dependent proteins or processes to define the amplitudes and time course of [Ca 2ϩ ] i elevations. In the squid giant axon (Adler et al, 1991) and frog hair cells (Roberts et al, 1990), this approach has supported the theoretical expectation that [Ca 2ϩ ] i elevations during Ca 2ϩ influx are large and rapid. Furthermore, these studies have suggested that particular Ca 2ϩ -dependent processes are coupled closely to sites of Ca 2ϩ influx.…”
supporting
confidence: 53%
“…There is evidence for CaK channels colocalized with the Ca 2ϩ channels in the frog NMJ terminal (Robitaille and Charlton, 1992;Robitaille et al, 1993). It is therefore possible that perhaps 30 -50% of the particles in the AZ are CaK channels, similar to the AZs of hair cells (Roberts et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…These rapid, high transients produce the rapid exocytosis of vesicles containing neurotransmitter substances from presynaptic nerve terminals (Simon and Llinas, 1985;Zucker and Fogelson, 1986;Roberts et al, 1990;Augustine et al, 199 1;Llinas et al, 1992). Dissipation of these transients by diffusion and buffering adds a small Ca*+ load to the longer-lasting spatially uniform [Ca*+],-termed the residual free calcium concentration-of the terminal.…”
Section: Discussionmentioning
confidence: 99%